How Do Theist (Muslim) Pre-Service Science Teachers Reconcile Their Individual Ontologies with Premises of Modern Science - Halil Turgut (Seyit Ahmet Kıray, 2019)
The purpose of this study was to investigate how theist (Muslim) pre-service science teachers' reconcile their individual ontologies, which stem from their worldviews, with premises of modern science. 23 pre-service science teachers (10 males and 13 females, ages ranged from 19 to 23) were selected by purposeful sampling. Data sources included open-ended questions and semi-structured follow-up interviews. The qualitative analysis of data revealed that theist participants believing in a created Nature which is being lawful and understandable but also open to supernatural intervention diverged in their perspectives about the ontological premises that scientists must have and presupposed theism, theism/naturalism or just naturalism for doing science. They all asserted the physical universe as the boundary for science and evaluated the possibility of the scientific investigation of miracles and jinn within that boundary with the criterion of being able to obtain empirical data. They did not perceive any incompatibility between science and Islam and proposed methodological naturalism for scientific practice in order to overcome potential conflicts.